The Transformation of Distance Learning: Technological Challenges and Opportunities in Digital Era - Rahmawati, Devie; Anindhita, Wiratri; Viendyasari, Mila; Lukmanto, Giri (CV. Media Digital Publikasi Indonesia, 2026)
This study aims to analyse the transformation of distance learning during and after the pandemic Covid-19. The study used qualitative approach using a case study design. The participants in this study are 10 communication studies students currently in their second year. Data collection for this study was carried out through interviews and a literature review. In-depth interviews were conducted in three stages. Data analysis was carried out through the stages of data collection, data selection, data analysis, and the formulation of conclusions. The results of this study indicate that distance learning has transformed learners, enabling them to adapt to technology. The use of technology is not limited to entertainment but also supports the learning process. However, not all learners feel comfortable with distance learning. This is because every student has a different learning style. This study concludes that the transformation of distance learning must be aligned with students’ learning styles. Furthermore, distance learning must be able to build students’ self-confidence and collaborative skills. Consequently, they can identify opportunities to adapt to learning in the digital age.